Detection of Dibutyl Phthalate in Surface Water by Fluorescence Polarization Immunoassay - Liliya I. Mukhametova; Madina R. Karimova; Olga G. Zharikova; Andrey V. Pirogov; Valentina V. Levkina; Ekaterina S. Chichkanova; Liqiang Liu; Chuanlai Xu; Sergei A. Eremin (Biosensors, 2023)
Dibutyl phthalate (DBP) is widely used as a plasticizer in the production of polymeric materials to give them flexibility, strength and extensibility. However, due to its negative impact on human health, in particular reproductive functions and fetal development, the content of DBP must be controlled in food and the environment. The present study aims to develop a sensitive, fast and simple fluorescence polarization immunoassay (FPIA) using monoclonal antibodies derived against DBP (MAb-DBP) for its detection in open waters. New conjugates of DBP with various fluorescein derivatives were obtained and characterized: 5-aminomethylfluorescein (AMF) and dichlorotriazinylaminofluorescein (DTAF). The advantages of using the DBP-AMF conjugate in the FPIA method are shown, the kinetics of binding of this chemical with antibodies are studied, the analysis is optimized, and the concentration of monoclonal antibodies is selected for sensitivity analysis—16 nM. The calibration dependence of the fluorescence polarization signal for the detection of DBP was obtained. The observed IC50 (DBP concentration at which a 50% decrease in the fluorescence polarization signal occurs, 40 ng/mL) and the limit of detection (LOD, 7.5 ng/mL) values were improved by a factor of 45 over the previously described FPIA using polyclonal antibodies. This technique was tested by the recovery method, and the high percentage of DBP discovery in water ranged from 85 to 110%. Using the developed method, real water samples from Lake Onega were tested, and a good correlation was shown between the results of the determination of DBP by the FPIA method and GC-MS. Thus, the FPIA method developed in this work can be used to determine DBP in open-water reservoirs.